Neuroinflammatory Triangle Presenting Novel Pharmacological Targets for Ischemic Brain Injury - Shaheryar, Zaib A.; Khan, Mahtab A.; Adnan, Ch. Sherjeel; Zaidi, Awais Ali; Hänggi, Daniel; Muhammad, Sajjad (Frontiers in Immunology, 2021)
Ischemic stroke is one of the leading causes of morbidity and mortality globally. Hundreds of clinical trials have proven ineffective in bringing forth a definitive and effective treatment for ischemic stroke, except a myopic class of thrombolytic drugs. That, too, has little to do with treating long-term post-stroke disabilities. These studies proposed diverse options to treat stroke, ranging from neurotropic interpolation to venting antioxidant activity, from blocking specific receptors to obstructing functional capacity of ion channels, and more recently the utilization of neuroprotective substances. However, state of the art knowledge suggests that more pragmatic focus in finding effective therapeutic remedy for stroke might be targeting intricate intracellular signaling pathways of the ‘neuroinflammatory triangle’: ROS burst, inflammatory cytokines, and BBB disruption. Experimental evidence reviewed here supports the notion that allowing neuroprotective mechanisms to advance, while limiting neuroinflammatory cascades, will help confine post-stroke damage and disabilities.